1996
DOI: 10.1093/fampra/13.3.264
|View full text |Cite
|
Sign up to set email alerts
|

Shared care: a review of the literature

Abstract: This review examines broad issues of concern regarding the primary/secondary care interface. The main purpose was to identify areas of good practice which could be adapted for more general use. One of the most fundamental aspects identified was communication, which is discussed in some detail. Also covered are shared prescribing and disease management. The data suggest that the most effective system(s) of shared care has yet to be established. Further qualitative and economic evaluations are required, taking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 104 publications
1
41
0
1
Order By: Relevance
“…9 Studies on communication across sector boundaries in paediatric oncology have shown that an information package may effectively improve communication between the oncology unit and the GP. 10 Our results support these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Studies on communication across sector boundaries in paediatric oncology have shown that an information package may effectively improve communication between the oncology unit and the GP. 10 Our results support these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The dialogue between the oncologist and the GP is particularly important. [7][8][9] James et al 10 reported that a paediatric oncology information package for GPs helped them to manage their patients' disease and improved their communication with the oncologists.…”
mentioning
confidence: 99%
“…A wealth of evidence points to the importance of productive interactions and cooperation in developing, maintaining and updating team care plans, and making that common care plan available for all providers and the patient [27][28][29].…”
Section: Developing and Maintaining Care Plans With Teams And Patientsmentioning
confidence: 99%
“…In different areas of health care, integrated care delivery systems have proven beneficial to patients' health and financial resources [7][8][9][10][11][12] by reducing hospital stays 8 and costs 7,12 and by improving patient and provider satisfaction. 7 However, in largely rural states such as NC, HIV health and social services are fragmented.…”
Section: Synopsismentioning
confidence: 99%